2018
DOI: 10.3920/978-90-8686-875-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated approaches to health

Abstract: Challenges calling for integrated approaches to health, such as the One Health (OH) approach, typically arise from the intertwined spheres of humans and animals, and the ecosystems constituting their environment. Initiatives addressing such wicked problems commonly consist of complex structures and dynamics. The Network for Evaluation of One Health (NEOH) proposes an evaluation framework anchored in systems theory to address the intrinsic complexity of OH initiatives and regards them as subsystems of the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 68 publications
(95 reference statements)
0
11
0
Order By: Relevance
“… Milen Georgiev (EFSA SCER Unit) created a query-poll for the participants, asking 6 questions on how far participants' countries had developed 'One Health' approaches, based on a suggested conceptual assessment of 'One Health-ness' (Rüegg, SR et al, 2018;Chapter 3.5). The results are shown in Figure 1 below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Milen Georgiev (EFSA SCER Unit) created a query-poll for the participants, asking 6 questions on how far participants' countries had developed 'One Health' approaches, based on a suggested conceptual assessment of 'One Health-ness' (Rüegg, SR et al, 2018;Chapter 3.5). The results are shown in Figure 1 below.…”
Section: Discussionmentioning
confidence: 99%
“…Cecile Aenishaenslin advised that the concept of a 'One Health' Survey (Rüegg, SR, et al, 2018;Chapter 3.5) is an excellent starting point to encourage government departments to take 'One Health' seriously.…”
Section: Discussionmentioning
confidence: 99%
“…Only one economic evaluation study was found (Zinsstag et al, 2007), with such information being crucial for decisionmakers to consider the cost and utility impacts of different biosecurity intervention. More cross-sectoral intervention evaluations that incorporate both epidemiological and economic impacts are needed to ensure efficient intervention selection (Rüegg et al, 2018).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Two evaluation tools were employed: a) the NEOH tool assesses the "One Health-ness" of initiatives with a catalogue of ∼80 semi-quantitative questions about knowledge integration (12). The tool was later scrutinised in a more generic context.…”
Section: Evaluation Tools Procedures and Data Processingmentioning
confidence: 99%
“…With the Checklist for One Health Epidemiological Reporting of Evidence (COHERE) a benchmark of reportable elements was stated that should promote the integration of knowledge from the domains of humans, animals and their environment (10). In another attempt, the EU COST Action (TD1404) "Network for Evaluation of One Health (NEOH)" characterised OH and proposed a framework to assess the added value of integrated approaches by comparing knowledge integration (assessed with a specific tool) to the outcomes achieved or expected from the theory of change of a given initiative (11,12). A method for evaluating knowledge integration capacity in multi-stakeholder governance (EVOLvINC) was derived from the NEOH tool in collaboration with experts from transdisciplinary research, sustainability sciences, and international development research (13,14).…”
Section: Introductionmentioning
confidence: 99%